2010
DOI: 10.1038/jp.2010.1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal consumption of polyphenol-rich foods in late pregnancy and fetal ductus arteriosus flow dynamics

Abstract: We read with interest the article by Zielinsky et al. 1 , and we have some questions about the study methods and conclusions.In this paper, Zielinsky et al. 1 show alterations in ductal dynamics in fetuses exposed to polyphenol-rich foods and argued that maternal consumption of polyphenol-rich food is a risk factor for ductal constriction.Our first concern is related to the study design: was it a prospective study or a transversal study? The relative risks were adjusted for gestational age?Although the paper s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…I thank you for giving me the opportunity to comment on the letter by Galão et al 1 regarding our article published in the Journal of Perinatology. 2 As Galão et al state, we have demonstrated alterations in ductal dynamics when normal fetuses were exposed to a high maternal intake of polyphenol-rich foodsFabove the 75th centile for our populationFand we indeed do hypothesize that these alterations may be a risk factor for ductal constriction, even though this issue was not the object of the present investigation.…”
mentioning
confidence: 99%
“…I thank you for giving me the opportunity to comment on the letter by Galão et al 1 regarding our article published in the Journal of Perinatology. 2 As Galão et al state, we have demonstrated alterations in ductal dynamics when normal fetuses were exposed to a high maternal intake of polyphenol-rich foodsFabove the 75th centile for our populationFand we indeed do hypothesize that these alterations may be a risk factor for ductal constriction, even though this issue was not the object of the present investigation.…”
mentioning
confidence: 99%